Hubungan antara tingkat pengetahuan orang tua tentang maloklusi dengan kebutuhan perawatan ortodonti interseptif - Yohana Yusra; Rena Bernadet (Fakultas Kedokteran Gigi Universitas Trisakti, 2023)
Background: Malocclusion is a deviation from normal occlusion and the third priority dental health issue. Interceptive orthodontics is a treatment for reducing malocclusion. Knowledge of malocclusion by parents can affect whether or not their children require orthodontic treatment. Aim: Determining the correlation between parental understanding of malocclusion and the necessity for interceptive orthodontic treatment among Primary School of Sang Timur students in East Jakarta. Method: This sort of research was an analytic observational study, using a cross-sectional design. The examination was conducted using the IKPO-I form and a modified questionnaire from Pravara Institute of Medical & Rural Dental College, Loni, India. Result The findings demonstrated that 48 parents (46.6%) of the 103 students and parents at Primary School of Sang Timur Elementary in East Jakarta had a good knowledge of malocclusion; on the other hand, 26 parents (25%) had less understanding. Examining the participants using the IKPO-I revealed that 17 (16,5%) did not require orthodontic treatment; 57 (55,3%) need interceptive orthodontics and the other hand, 29 (28.1%) need corrective orthodontic treatment. Conclusion: Based on the findings of this study, there is no correlation between parental knowledge of malocclusion and the requirement for interceptive orthodontic treatment.